Czy z obrazu językowego można wyinterpretować, na czym polega istota etyki społecznej? = Can Be Interpreted from the Image of the Language, What is the Essence of Social Ethics? - Kaczor, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Established connections of word expression of with concepts related to social ethics reveals the ontological dimension of conceptualization of ethical and social attitude. Imaginative schemes that are used for imaging the moral order of society, show what is important for the internal (spiritual) and external (physical) dimension of social ethics. They perpetuate the values actually experienced by people and based on their ethical behaviour.
Keywords: moralność; etyka; językowy obraz świata; konceptualizacja; metafory językowe; morality; ethics; language picture of the world; conceptualization; linguistic metaphors